THE INTERNATIONAL LEGAL PERSONALITY OF TRANSNATIONAL CORPORATIONS: THE “SUBJECT OR OBJECT OF LAW” DEBATE AND THE POSSIBILITY OF HOLDING THEM LEGALLY RESPONSIBLE BY STATES - Mansurov, Shohsaidkhon (Oriental Journal of History, Politics and Law, 2026)
There is little doubt today that transnational corporations (TNCs) have become among the most powerful actors in the global economy. In some cases, their economic capacity equals or even exceeds that of many sovereign states. Nevertheless, their legal status and international legal personality remain among the most controversial issues in the theory of international law. According to the traditional approach, states are the primary and full subjects of international law, whereas transnational corporations are regarded not as direct subjects of international law but rather as objects of its regulation. This article examines the longstanding “subject or object of law” debate concerning the international legal status of transnational corporations based on leading scholarly perspectives and demonstrates that the issue is of not only theoretical but also significant practical importance. This is because the recognition of a corporation's international legal personality determines whether it may be held directly responsible under international law for violations of international legal norms. The article analyzes the emergence and development of the theory of international legal personality, including the approaches derived from the International Court of Justice’s 1949 Advisory Opinion in Reparation for Injuries Suffered in the Service of the United Nations (“Reparations”). It further provides a comparative legal analysis of the principal doctrinal approaches to the international legal status of transnational corporations, including the traditional approach, the revisionist approach, the concepts of direct and indirect international obligations, as well as skeptical and functional approaches. The findings indicate that transnational corporations currently possess a limited degree of participation in the international legal system. In particular, international investment arbitration enables corporations to bring direct procedural claims against states; international soft law establishes standards of corporate conduct; and the draft legally binding international treaty on business and human rights currently being negotiated within the United Nations seeks to establish direct international obligations for corporations. The article concludes by assessing the practical significance of this theoretical debate for the Republic of Uzbekistan.